Snowshoe Thompson - Levinson, Nancy Smiler; Sandin, Joan ([New York] : HarperCollins Publishers, 1992)
One winter John Thompson skis across the Sierra Nevada Mountains and creates a path upon which mail and people may travel, thus earning his nickname "Snowshoe Thompson."
Keywords: Thompson, Snowshoe, -- 1827-1876 -- Juvenile literature; Frontier and pioneer life -- Sierra Nevada Region (California and Nevada) -- Juvenile literature